MODEL PEMBELAJARAN TREFFINGER BERBANTU APLIKASIWORDWALL TERHADAP KEMAMPUAN PEMECAHANMASALAH MATEMATIS PESERTA DIDIKDI SMA N1 AIR BATU - Nuraini; Muthia Dewi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The aims of this study is to determine the effect of the Treffinger Learning model assisted by the Wordwall application on the mathematical problem-solving abilities of students at SMA N 1 Air Batu. This study is a quasi-experimental study with a Two Group Pretest-Posttest Design. The population in this study was  the entire tenth grade, consisting of five classes. The sample consisted of two classes (Xth-1 and Xth-2) selected using cluster random sampling. Xth-1 class served as the control class using the conventional learning model, while Xth-2 class served as the control class using the Treffinger Learning model. After the instruction is completed, a posttest is conducted, showing the average results for the experimental 53,793 and control classes 40,459. The t-test results tcount = 8,057>ttable=2,003 so Ho is rejected and H1 accepted, indicating the influence of the Treffinger Learning model assisted by the Wordwall application on the mathematical problem-solving abilities of students at SMA N 1 Air Batu.